Auditoria de Gestion al Gobierno Autonomo Descentralizado Parroquial de Vilcabamba, periodo 2021 - León Ortega, Jhoselyn Nathaly (2023)
The curricular integration work entitled Management Audit of the Vilcabamba Parish Decentralized Autonomous Government, period 2021, was developed to evaluate the internal control system carried out by the institution based on current regulations, as well as the degree of compliance with the programs, projects and optimal management of resources through the application of management indicators within the economy, efficiency and effectiveness of resources. Procedures were applied that allow achieving the silver objectives and complying with the phases of the management audit; starting with the Preliminary Knowledge where visits were made to the entity to collect information such as the POA, institutional organization chart, list of officials, legal regulations and other necessary documentation; consecutively the planning in order to review, analyze and process the information collected, the different matrices, objectives, focus and reason for the audit were elaborated; Continuing with the phases we have the execution is the most highlighted phase of the work since in it the application of the different procedures established in the Audit Program is carried out, it was evaluated the internal control of the institution were found that were raised in the narrative cards, thus management indicators were also applied to measure the degree of efficiency, effectiveness of the programs and projects carried out in the entity, they were described in analytical cards; the Communication of Results where a final audit report was prepared including comments, conclusions, and recommendations of each of the areas evaluated, which are made available to the entity to make decisions that help achieve the objectives and goals; finally Follow-up where a schedule was prepared to detail the activities necessary to comply with the aforementioned recommendations. After having concluded the work of curricular integration, it was specified that no breach of the current legal regulations for entities belonging to the public sector has been observed, which has caused the activities carried out in the institution not to reach the goals set and that the optimization of resources is not effective and efficient, the same thing that was raised in recommendations to take corrective actions for the benefit of the Vilcabamba Parish GAD.